Crime and poverty: evidence from a natural experiment - Fafchamps, M; Minten, B (University of Oxford, 2002)
This paper investigates the relationship between poverty and crime. Following a disputed presidential election, fuel supply to the highlands of Madagascar was severely curtailed in early 2002, resulting in a massive - if temporary - increase in poverty. Using original survey data collected in June 2002 at the height of the crisis, we find that crime increases with poverty. Our most conclusive results are for crop theft. We also find that an increase in law enforcement personnel reduces cattle theft which, in Madagascar, is a form of organized crime. Theft appears to be used by some of the rural poor as a risk coping strategy. Increased transport costs led to a rise in cattle and crop theft, suggesting that isolation raises crime.